Geomagnetic Activity Control of Irregularities Occurrences Over the Crests of the African EIA. Issue 7 (14th July 2020) - Amaechi, P. O.; Oyeyemi, E. O.; Akala, A. O.; Amory‐Mazaudier, C.
Abstract: This paper investigated the behavior of ionospheric irregularities over the African equatorial ionization anomaly (EIA) crests during intense geomagnetic storms that occurred from 2012 to 2015. Irregularities were monitored using the rate of change of TEC index along with variations of the horizontal component of the Earth's magnetic field (H) and ionospheric electric current disturbance (Diono). The predictive capability of the Prompt Penetration Equatorial Electric Field Model (PPEFM) was assessed by comparing prompt penetration electric field (PPEF) inferred from interplanetary electric field and Diono with PPEF derived from the PPEFM, with emphasis on how well the model reproduced enhancement/reduction in the prereversal enhancement (PRE). Eastward PPEF triggered short duration irregularities on 23 April 2012, 17 March 2013, and 20 February 2014 while westward electric field reduced them thereafter. The PPEFM rightly predicted enhancement (reduction) in PRE on 17 March 2013 (19 February 2014) when irregularities were triggered (inhibited). It, however, showed no change in the PRE on 23 April 2012 and 20 February 2014. During the storms recoveries, irregularities were always inhibited/reduced over the trough by westward disturbance dynamo and the inhibition lasted longer during the superstorm of March 2015. Also, there was a hemispheric asymmetry in irregularities over the African EIA crests. On 16–17 July 2012, 15 November 2012, and 19 March 2013, there were differences in irregularities behavior. On these days, the asymmetry of the postsunset crests was pronounced in both hemispheres. Key Points: During intense storms, the combined effect of PPEF and DDEF modulated the behavior of ionospheric irregularities over the crests of the Africa EIA Irregularities over the African EIA crests exhibited a pronounced hemispheric asymmetry during the recovery phase of intense storms The predictive capability of the Prompt Penetration Equatorial Electric Field Model is assessed over Africa during intense storms